The effect of heel elevation on the stiffness gradient index of the digital flexor tendons in the equine forelimb of clinically normal horses - Shaw, Kelly A.; Brounts, Sabrina H. (Frontiers in Veterinary Science, 2025)
ObjectiveTo evaluate the effect of heel elevation on in vivo measurement of stiffness gradients by means of acoustoelastography in the digital flexor tendons of clinically normal horses.Animals15 clinically normal horses.ProceduresFor each horse, stiffness gradient index (SGI) for superficial digital flexor tendons (SDFT) and deep digital flexor tendons (DDFT) were evaluated in both forelimbs at 0, 4 and 8 degrees of heel elevation. Acoustoelastography (AEG) was used for data acquisition at three sites, approximately 6, 12, and 18 cm distal to the accessory carpal bone in the metacarpal region. Lifting the contralateral limb during image acquisition resulted in the application of load and the subsequent SDFT and DDFT deformation required. The effects of loaded versus unloaded digital flexor tendons and right-to-left limb symmetry on SGI at three regions in the metacarpal region were further evaluated. Changes in angulation of the metacarpophalangeal, proximal interphalangeal, and distal interphalangeal (DIP) joints in conjunction with the palmar angle (PA) of the distal phalanx and toe angle (TA) were measured radiographically at 0, 4 and 8 degrees of heel elevation to approximate trends in digital angles with applied heel elevation.ResultsSGI values for SDFTs and DDFTs differed significantly in loaded versus unloaded tendons and at different locations of the metacarpus. Incremental heel elevation had the greatest and most consistent effect on the SGI in the mid-metacarpal region in both flexor tendons. At this level, the stiffness gradient tended to decrease when the angle of heel elevation increased from 0 to 8 degrees for both flexor tendons. There was a significant difference in SGI between loading and unloading the limb during AEG acquisition, with reduced variability when the digital flexor tendons were loaded.Conclusions and clinical relevanceResults indicated that the SGI of digital flexor tendons was significantly affected by heel elevation. Regarding technique, AEG can be easily and effectively utilized to measure flexor tendon strain in a standing horse with applied heel elevation. This model resulted in direct quantification of tendon strain as it relates to distal limb conformation, which would allow for more targeted therapeutic farriery techniques.